БАЗАР ЭКОНОМИКАСЫНА ӨТИЎ ДӘЎИРИНДЕ ҚАРАҚАЛПАҚСТАН САНААТЫНДА ЭКОНОМИКАЛЫҚ ӨЗГЕРИСЛЕР - Сарыбаев, А.К. (FAN va JAMIYAT, 2024)
This article shows the difficult economic situation of industrial factories of the Republic of Karakalpakstan during the transition to a market economy. The processes of economic transformation of the industrial sector of the region in the 90s of the twentieth century are also reflected on the path of economic reforms.